PERAN DINAS PARIWISATA PROVINSI SUMATERA BARAT DALAM MEWUJUDKAN WISATA HALAL - Rahma Dira Ismail; M. Fachri Adnan (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
Halal tourism is one of the programs that have been launched by the Sumatra Provincial Government to attract international and domestic tourists since 2016. But until now there has not been any concrete efforts made by the Padang city government in realizing halal tourism in the city of Padang. This study aims to explain the role carried out by the West Sumatra Province Tourism Office in realizing halal tourism in West Sumatra, especially in the city of Padang, which is the capital of the province of West Sumatra, as well as knowing how the obstacles that occur when applying in realizing halal tourism in the city of Padang. This research uses qualitative research type by using descriptive method which is done by purposive sampling. Data collection techniques were carried out with interviews and documentation studies, with informants from several employees of the West Sumatra Province Tourism Office and several stakeholders related to the development of halal tourism in the city of Padang. The role and effort undertaken by the West Sumatra Province Tourism Office is still in the form of providing halal certification to restaurants and restaurants in the city of Padang. The absence of regulations governing halal tourism for regions and regencies in West Sumatra has caused the slow development of halal tourism.